Proposed Training Program to Develop Strength in Handball Players: A Field Study of Students at the Institute of Physical and Sports Activity Sciences and Techniques - herizi, abdelhadi (sports creativity, 2025)
Sport is one of the important human activities, as hardly any human society is devoid of some form of sport, regardless of the level of progress or backwardness of that society. Handball, like other team sports, emerged or came about as a result of the need for a new game for a particular group of individuals. In its current form, it is one of the competitive games practiced in international and Olympic competitions, attracting many spectators due to it being a ball game that has distinct characteristics setting it apart from other team sports. This type of sport has also come to rely on designing and planning scientifically studied training programs to develop all aspects of the game—technically, physically, and strategically—to improve performance levels. Generally, sports training, and physical preparation in particular, has become a broad concept based on systematic and scientific foundations built upon strict scientific principles, aiming for the player to acquire good physical fitness that allows the performance of various skills with ease. Among the most important basic physical qualities for a handball player is strength, which receives special attention in training programs. The results of which only appear if subjected to serious work, as a handball player must have strong throwing arm power in order to perform passing and shooting skills... and thus score as many points as possible as well as make good passes, which leads to positive results at various levels. This is what made us seriously consider studying this trait to demonstrate the effect of a proposed training program on developing strength in handball players.